Analisis Komponen Kamus Arab-Indonesia Karya Mahmud Yunus Perspektif Ali Al-Qasimy / Analysis of the Components of Kamus Arab-Indonesia by Mahmud Yunus Based on Ali Al-Qasimy's Perspective - Ica Amelia; Abdul Muntaqim Al Anshory; Rohmatulloh Salis (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
Dictionaries serve as a reference for individuals to understand word meanings, expand vocabulary, preserve languages, and support the ever-evolving global transmission of knowledge. Experts have established specific components that make a dictionary ideal and ready for use. This study aims to analyze the completeness of the components in Kamus Arab-Indonesia by Mahmud Yunus based on Ali Al-Qasimy’s perspective. The research employs a descriptive qualitative method with a library research approach. The primary data were obtained from Kamus Arab-Indonesia by Mahmud Yunus using documentation, reading, and note-taking techniques. The collected data were analyzed using qualitative data analysis techniques, including data reduction, data presentation, and conclusion drawing. The research results indicate that the Kamus Arab-Indonesia by Mahmud Yunus, based on Ali Al-Qasimy's perspective, qualifies as a fairly comprehensive dictionary in terms of its component completeness. This dictionary fulfills 22 out of the 27 dictionary components identified.. Thus, this dictionary is categorized as comprehensive in terms of its component completeness. This research contributes to the development of Arabic lexicography and serves as a reference for dictionary compilers to enhance the quality and comprehensiveness of their works. Additionally, it assists dictionary users in utilizing dictionaries more effectively. Based on the research findings, it is recommended that Arabic dictionary compilers pay closer attention to dictionary components to improve their quality and functionality. A more comprehensive dictionary would greatly support academic needs, whether in Arabic language learning or research.Abstrak: Kamus merupakan referensi bagi setiap orang untuk memahami makna kata, mengembangkan kosakata, melestarikan bahasa, dan mendukung transmisi global yang terus berkembang. Para ahli telah menetapkan komponen-komponen kamus agar kamus menjadi ideal dan siap untuk digunakan. Penelitian ini bertujuan untuk menganalisis kelengkapan komponen Kamus Arab-Indonesia Karya Mahmud Yunus Perspektif Ali Al-Qasimy. Penelitian ini merupakan penelitian deskriptif kualitatif dengan pendekatan studi pustaka. Data utama diperoleh dari Kamus Arab-Indonesia Mahmud Yunus dengan menggunakan teknik dokumentasi, baca, dan catat. Data yang dikumpulkan dianalisis dengan teknik analisis data kualitatif, berupa reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa Kamus Arab-Indonesia karya Mahmud Yunus berdasarkan perspektif Ali Al-Qasimy termasuk kamus yang cukup lengkap dari aspek kelengkapan komponennya. Kamus ini memenuhi kelengkapan 22 dari 27 komponen kamus yang ditetapkan. Penelitian ini memberikan kontribusi pada pengembangan ilmu leksikografi arab dan dapat menjadi referensi bagi penyusun kamus untuk meningkatkan kualitas dan komprehensivitas kamus, serta membantu pengguna kamus memanfaatkan kamus dengan lebih efektif. Berdasarkan hasil penelitian, disarankan agar penyusun kamus bahasa Arab memperhatikan komponen-komponen kamus guna meningkatkan kualitas dan fungsionalitas kamus. Penyusunan kamus yang lebih komprehensif akan sangat bermanfaat untuk mendukung kebutuhan akademik, baik dalam pembelajaran bahasa Arab maupun penelitian.